Rehabilitation of abandoned housing projects in Peninsular Malaysia: Lessons for housing entrepreneurs - Md Dahlan, Nuarrual Hilal (Academy for Global Business Advancement (AGBA), 2010)
Abandoned housing projects is one of the housing problems in Peninsular Malaysia. Even though there are laws and policies provided by the Malaysian government to govern housing industry, yet abandoned housing projects problem is still an unsettled issue for the Malaysian government to tackle.The real victims are the purchasers themselves. Virtually, there is no specific and common ways to face the problems of abandoned housing projects.This is due to the fact that in each and every abandoned housing project, the problems and issues faced by the stakeholders vary.This paper will discuss the law and practice in the rehabilitation of abandoned housing projects in Peninsular Malaysia.From the discussion, certain suggestions will be forwarded at the end part of the paper for facilitating the implementation of the rehabilitation of abandoned housing projects in Peninsular Malaysia by the housing entrepreneurs.